Query acceleration in distributed database systems - Haraty, Ramzi A.; Fany, Roula C. (Revista Colombiana de Computación, 2001)
The advent of telecommunication era and the constant development of hardware and network structures have encouraged the decentralization of data while increasing the needs to access information from different sites.